Ectopic expression of GATA6 bypasses requirement for Grb2 in primitive endoderm formation - CAPO-CHICHI, D. CALLINICE (My University, 2011)
Gene knockouts in mice have showed that Grb2 and GATA6 are essential for the formation of primitive endoderm in blastocysts. Here, we confirmed that implanted Grb2-null blastocysts lack primitive or extraembryonic endoderm cells either at E4.5 or E5.5 stages. We analyzed the relationship between Grb2 and GATA6 in the differentiation of embryonic stem (ES) cells to primitive endoderm in embryoid body models. Upon transfection with GATA6 expression vector, Grb2-null ES cells underwent endoderm differentiation as indicated by the expression of the extraembryonic endoderm markers Dab2 and GATA4. Transfection of GATA4 expression vector also had the same differentiation potency. When GATA6- or GATA4-transfected Grb2-null ES cells were allowed to aggregate, fragments of an endoderm layer formed on the surface of the spheroids. The results suggest that GATA6 is downstream of Grb2 in the inductive signaling pathway and the expression of GATA6 is sufficient to compensate for the defects caused by Grb2 deficiency in the development of the primitive and extraembryonic endoderm
Keywords: GATA6; Grb2; primitive; endoderme